Evolution of stomach cancer mortality in Brazil and its regions, by sex, 2011-2015 (Research, Society and Development, 2022)
To describe the distribution pattern of the stomach cancer mortality rate in Brazil and its regions, according to sex, between the year 2011 and 2015. Mortality values were described by the DATASUS atlas mortality and stratified by sex in the year 2011 and 2015 and analyzed by the Two-Way Anova test. It was observed that there was a higher mortality incidence in the Southeast and lower in the Midwest for both sexes. The Northeastern region presented a high number of cases standing out in relation to the North, Center-west and South regions (P